Cryopreserved platelets and their suitability in being re‐suspended in additive solution. Issue 8 (23rd September 2020) - McLean, Colin; McMillan, Loraine; Petrik, Juraj; Fraser, Alasdair R.; Morrison, Alex
Abstract : Background: Cryopreserved platelets are generally produced and stored in plasma. With the advent of additive solutions being routinely used it would be prudent to examine producing and storing these units in a platelet additive solution (SSP+). Study design and methods: Platelet concentrates were prepared from twenty overnight held whole blood units with 10 being re‐suspended in 100% plasma and 10 in approximately 70% SSP + and 30% plasma. All had 6% v/v DMSO added prior to storage at −80°C. On thawing plasma stored platelets were re‐constituted in fresh plasma with additive prepared platelets being subsequently suspended in 100% SSP+. Sample analysis was assessed pre cryopreservation, post thaw and 4 h. Results: We noted a significant increase in our annexin V levels along with a decrease in GP1bα Von Willebrand binding sites post thaw. The platelets ability to change shape was also significantly reduced as observed with our HSR and ESC values. However, despite this there was still sufficient material within the platelet to allow them to be viable as observed with our thromboelasticity results which, were still observed to be within normal parameters post thaw We also observed an increase in Extracellular vesicles post thaw, suggesting platelet damage which was supported by the reduction in platelet counts. Although there were still sufficient numbers to meet the minimum requirements of the UK guidelines.